Diagnóstico de fluoreto nas águas do Sistema Aquífero Guarani na região de Santa Maria, Rio Grande do Sul - Terra, Lueni Gonçalves (2015)
In the recent years there has been a constant discussion between the others and leading researchers in health and the world's environment, which are the benefits (inhibition of caries and dental enamel remineralization) and harm (dental fluorosis and skeletal fluorosis, mostly) by ingestion of fluoride in drinking water. Thus, the objective of this study was to diagnose fluoride anomalies and sort outcrop zone waters of the Guarani Aquifer System, in cities in the Central Region of Rio Grande do Sul. Therefore, the specific objectives were defined: Firstly, recognize the municipalities located in the Central Depression, with occurrences of anomalies in fluoride concentrations in groundwater. This study was done through research on the Company's website for Research on Mineral Resources (CPRM), selecting some funding for field sampling; Identifying fluoride anomalies from the results of chemical analyzes of samples; Sort the waters sampled in Piper diagram and Stiff diagrams and apply statistical method of correlation to find possible correlations, especially between electrical conductivity and fluoride. There were performed in total, twenty collections in the cities of Dona Francisca, Faxinal do Soturno, Restinga Seca, Santa Maria and São João do Polêsine. Among the twenty samples, twelve of them pointed fluoride index greater than the Maximum Allowed by law. Eighteen samples were identified as moles. In the chemical classification, eight samples proved bicarbonate with sodium, seven had sodic chlorinated and five mixed sodium. The statistical processing pointed out that there is no significant correlation between conductivity and fluoride. It is concluded that there is need for further work on the subject. In addition, the water knowledge with fluoride anomalies in other municipalities is essential for public health problems to be controlled and/or prevented.